ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA PT. BPR WELERI MAKMUR JAWA TENGAH - Hedy Kuswanto; sukemi kamto sudibyo (LPPM STIE DHARMAPUTRA SEMARANG, 2011)
The aim of this research is to examine the relationships between influence factors and performance of accounting information system (AIS). AIS has the potensial to improve organizational performance however many systems in the process of being implemented may be classed as failures. So it's important to know how to minimize the failure of AIS development. Many factors are believed to affect the success of AIS performance. This study focused on User Accounting information System Stutisfaction, User Accountinglnformation Use, User Involvement, Capability of Inform allan System Personnel, Top Management Support, Formalization of Information System as influence factors and on AIS satisfaction and user system usage as surrogate of AIS performance.This research questionnaire is to be completes by users of the AIS in PT. BPR Weleri Makmur Jawa Tengah. The questionnaire were spread to staff Operation, Loan and Marketing. This research analytical device was a multiple regression to analyze the influence of independent variables toward dependent variables.Based on the research result of the empirical test suggested that there are significant correlations between the performance of AIS ang the influence factors as : User Accounting information System Stutisfaction, User Accounting Information Use, User Involvement, Capability of Inform allan System Personnel, Top Management Support, Formalization of Information System.Keywords : User Accounting information System Stutisfaction, User Accounting Information Use, User Involvement, Capability of Inform allan System Personnel, Top Management Support, Formalization of Information System, AIS Performance.